2005
DOI: 10.1038/sj.leu.2403844
|View full text |Cite
|
Sign up to set email alerts
|

Clonal selection in the bone marrow involvement of follicular lymphoma

Abstract: To characterize the pathways of bone marrow (BM) involvement of follicular lymphoma (FL), we performed morphological and immunophenotypical analysis of tumor cells from lymph nodes (LNs) and corresponding BMs in 21 patients with FL. In three cases, genealogical trees were constructed based on the immunoglobulin variable region heavy chain (IgV H ) gene sequences of tumor clones from LNs and BMs. Results showed that FLs within the BMs display identical or lower cytological grades than in the LNs. In the majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 33 publications
4
36
0
Order By: Relevance
“…Dissemination of FL clones among different lymph follicles and LN has been documented. [16][17][18][19]21,30 Studies showing that FL cells colonize non-neoplastic germinal centers and that non-neoplastic germinal centers can serve as a niche for FL cells are further supported by the concept of "in situ" FL, which represents infiltration of pre-existing non-neoplastic germinal centers by FL cells, rather than de novo formation of malignant germinal centers. 17,[31][32][33] Our conclusion that FL originates in the LN is consistent with the hypothesis of a possible dormant FL tumor stem cell harboring an unmutated, rearranged IgV H/L gene as part of the t(14;18)(q32;q21) translocation, which is possibly exposed to the somatic hypermutation machinery by passing the germinal centers of LN, acquiring additional point mutations and progressing to clinically overt FL.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Dissemination of FL clones among different lymph follicles and LN has been documented. [16][17][18][19]21,30 Studies showing that FL cells colonize non-neoplastic germinal centers and that non-neoplastic germinal centers can serve as a niche for FL cells are further supported by the concept of "in situ" FL, which represents infiltration of pre-existing non-neoplastic germinal centers by FL cells, rather than de novo formation of malignant germinal centers. 17,[31][32][33] Our conclusion that FL originates in the LN is consistent with the hypothesis of a possible dormant FL tumor stem cell harboring an unmutated, rearranged IgV H/L gene as part of the t(14;18)(q32;q21) translocation, which is possibly exposed to the somatic hypermutation machinery by passing the germinal centers of LN, acquiring additional point mutations and progressing to clinically overt FL.…”
Section: Discussionmentioning
confidence: 83%
“…6,10 Bognar et al indicated that the BM niche plays a decisive role in FL, suggesting early infiltration events from the LN compartment. 21 Applying the commonly used CLUSTALembedded multiple sequence alignment (MSA) algorithm, however, they were unable to delineate migration directions in relation to time. 36,37 A basic feature of MSA algorithms is to calculate the evolutionary distance of operational taxonomic units (OTU), for instance of the genetic distance of nucleotide sequences, by a pairwise comparison of all units.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, individual tumor cells can each have slightly different Ig variable region sequences. 5 Random mutations should eventually result in stop codons and loss of BCR protein expression. However, FL tumors maintain a surface BCR, indicating a selective force favoring retention of a functional BCR.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed a bone marrow-specific niche has already been proposed by several groups. [18][19][20] In consequence it could even be that clonally related and bone marrow-resident FLLC, instead of fully malignant FL cells, cause a relapse of lymphoma ( Figure 1E). …”
mentioning
confidence: 99%